PERAKITAN PUPUK ALAM BERBASIS SUMBERDAYA LOKAL UNTUK MENINGKATKAN EFISIENSI PEMUPUKAN P DAN K SERTA HASIL KEDELAI DI TANAH MASAM - Tufaila, Muh.; Alam, Syamsu (Jurnal Agroteknos, 2013)
The research aimed to formulate a natural fertilizer based on local resources to improve the efficiency of fertilizer P and K and yield of soybean in acid soils of Southeast Sulawesi. The research involved natural fertilizer formulations with mica schist rock materials, harzburgite, and rock phosphate, and further testing of fertilizers. Laboratory fertilizer testing was performed by experimental methods to determine the slow release properties and the amelioration capabilities of fertilizer. Fertilizer treatments were fertilizer of mica schist and rock phosphate without coating harzburgite (L0), semifagit fertilizer with coatings harzburgite 1 time (L1), semifagit fertilizer with coatings harzburgite 2 times (L2), and semifagit fertilizer with coatings harzburgite 3 times (L3). Further testing was fertilizers test on acid soils, soybean yield and fertilizer efficiency with experimental methods. The treatments were fertilizer factors consisting of two levels: fertilizer of mica schist and rock phosphate without harsburgit coatings and semifagit coated fertilizers best harzburgite on experiments in the laboratory, and fertilizer factor of five levels: 0%, 40%, 60%, 80%, 100% P2O5 kg.ha-1 of the recommended dosage (100 kg.ha-1). The research concluded that the natural fertilizer was slow release, use of harsburgit as the outer layer of fertilizer increased fertility of acid soils, fertilizers of mica schist and rock phosphate with coatings harsburgit 3 time (L3) was the best to amelioration of acid soil, the higher dose of fertilizer was followed by the higher the pH, total N, available P, exchangeable K, Mg, and CEC and the lower content of Al-dd soil; the use of semifagit fertilizer dose of 80% of the recommendated dose (100 kg P2O5.ha-1) gave a better effect on plant height, wet weight, dry weight, number of pods, weight of 10 seeds and soybean yield per hectare (2.74 ton.ha-1). The higher the dose of fertilizer was followed by the higher uptake of P and K, and the highest efficiency of fertilizer P and K was at 19.32% and 15.26% for fertilizer using semifagit with a dose of 80% of the recommended dose (100 kg P2O5.ha-1).